2012
DOI: 10.1556/oh.2012.29362
|View full text |Cite
|
Sign up to set email alerts
|

Carbon/carbon implants in oral and maxillofacial surgery – Part 2

Abstract: A szerzők előző közleményükben karbon/karbon állcsontimplantátumokkal kapcsolatos hosszú távú tapasztalataikról számoltak be. A jó funkcionális és esztétikai eredmények értékelése után a szervezet hatását vizsgálták az implantátum struktúrájára és morfológiájára nézve modern felületanalitikai módszerekkel. Nyolc év után eltávolított és be nem ültetett (referencia-) implantátumokat hasonlítottak össze. Mind a referencia-, mind a szervezetből eltávolí-tott implantátum két fő komponense a szén és az oxigén, azonb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The results showed that the C/C composite material has good hard tissue compatibility, and no fibrous tissue was formed between the bone tissue and the C/C composite. Then C/C composite was being applied in the field of medical research and became a hot research topic [19]. However, this material tends to produce carbon debris [20,21] produced by friction, resulting in inflammation risk and longer postoperative recovery period.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the C/C composite material has good hard tissue compatibility, and no fibrous tissue was formed between the bone tissue and the C/C composite. Then C/C composite was being applied in the field of medical research and became a hot research topic [19]. However, this material tends to produce carbon debris [20,21] produced by friction, resulting in inflammation risk and longer postoperative recovery period.…”
Section: Introductionmentioning
confidence: 99%